Cerebellar gamma-aminobutyric acid type A receptors: pharmacological subtypes revealed by mutant mouse lines - Makela,R; Uusi-Oukari,M; Homanics,GE; Quinlan,JJ; Firestone,LL; Wisden,W; Korpi,ER (Mol Pharmacol, 1997)
The vast molecular heterogeneity of brain gamma-aminobutyric acid type A (GABAA) receptors forms the basis for receptor subtyping. Using autoradiographic techniques, we established the characteristics of cerebellar granule cell GABAA receptors by comparing wild-type mice with those with a targeted disruption of the alpha6 subunit gene. Cerebellar granule cells of alpha6(-/-) animals have severe deficits in high affinity [3H]muscimol and [3H]SR 95531 binding to GABA sites, in agonist-insensitive [3H]Ro 15-4513 binding to benzodiazepine sites, and in furosemide-induced increases in tert-[35S]butylbicyclophosphorothionate binding to picrotoxin-sensitive convulsant sites. These observations agree with the known specific properties of these sites on recombinant alpha6beta2/3gamma2 receptors. In the presence of GABA concentrations that fail to activate alpha1 subunit-containing receptors, methyl-6,7-dimethoxy-4-ethyl-beta-carboline (30 microM), allopregnanolone (100 nM), and Zn2+ (10 microM) are less efficacious in altering tert-[35S]butylbicyclophosphorothionate binding in the granule cell layer of the alpha6(-/-) than alpha6(+/+) animals. These data concur with the deficiency of the cerebellar alpha6 and delta subunit-containing receptors in the alpha6(-/-) animals and could also account for the decreased affinity of [3H]muscimol binding to alpha6(-/-) cerebellar membranes. Predicted additional alterations in the cerebellar receptors of the mutant mice may explain a surplus of methyl-6,7-dimethoxy-4-ethyl-beta-carboline-insensitive receptors in the alpha6(-/-) granule cell layer and an increased diazepam-sensitivity in the molecular layer. These changes may be adaptive consequences of altered GABAA receptor subunit expression patterns in response to the loss of two subunits (alpha and delta) from granule cells.